Joint Surgery in Tunisian Rheumatoid Arthritis Patients: Prevalence and Risk Factors - Olfa SAIDANE,; Leila GAFSI,; Aicha Ben TEKAYA,; Ines MAHMOUD,; Rawdha TEKAYA,; Leila ABDELMOULA, (Archives of Rheumatology, 2020)
Objectives: This study aims to assess the prevalence of joint surgery in Tunisian patients with rheumatoid arthritis (RA) and to determine the risk factors of surgical treatment. Patients and methods: This retrospective cross-sectional study was performed over a period of 15 years between January 2000 and December 2014 and included 500 Tunisian patients with RA (78 males, 422 females; mean age 53.4 years; range, 21 to 83 years). The prevalence of joint surgery indication was evaluated. Clinical, paraclinical and therapeutic characteristics of RA were compared according to the need of surgery. Results: Female to male ratio was 5. The indication of joint surgery was noted in 59 patients (12%). Knee joint surgery was the most performed surgical procedure (56% of surgical treatment). A decrease in surgery prevalence from 30% in 2004 to 4% in 2013 was noted. Statistical study showed that factors associated with joint surgery were: delayed diagnosis (p=0.037), long RA duration (p=0.017), young onset of RA (p<0.001), presence of joint deformities (p=0.034), presence of osteoporosis (p=0.029), presence of antinuclear antibodies (p<0.001), combination therapy of methotrexate with other conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs) (p=0.001), short period of first medical treatment (p=0.012) and high erythrocyte sedimentation rate (ESR) (p=0.027). In multivariate analysis, three factors were independently related to the use of joint surgery: age at disease onset [odds ratio (OR): 2.799 95% confidence interval (CI): 1.49-5.22; p=0.01], high ESR level (OR: 2.807 95% CI: 1.5-5.24; p=0.01) and association of methotrexate with other csDMARDs (OR: 3.500 95% CI: 1.61-7.56; p=0.01). Conclusion: Twelve percent of RA patients needed joint surgical treatment. Predictive factors of surgery were age at disease onset, high ESR level and association of methotrexate with other csDMARDs.